PERANCANGAN IDENTITAS VISUAL DAN DESAIN KEMASAN UMKM GAPIT JABOK UNTUK MENINGKATKAN BRAND AWARENESS GENERASI MUDA - Azhar Salsabila Cahyono; Taufik Murtono (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2026)
The implementation of visual identity in the packaging design of Gapit Jabok MSME products in Plumpang District was carried out as an effort to increase young generation awareness of traditional food products. The main problem identified was the absence of a consistent visual identity and packaging design that could effectively attract young consumers. This study aimed to design a visual identity and packaging design that are more modern, communicative, and aligned with the characteristics of the target audience without eliminating the traditional values of the product. The method used in this research was Design Thinking, which consists of the empathize, define, ideate, prototype, and test stages, with data collection conducted through observation, interviews, literature studies, and questionnaires. The target interest review questionnaire involved 30 respondents, while the alternative logo review involved 31 respondents. The collected data were analyzed using the SWOT technique to identify the strengths, weaknesses, opportunities, and threats of Gapit Jabok MSME. The results showed that the implementation of visual elements such as logos, colors, typography, mascots, patterns, and a consistent packaging system was able to enhance the product’s visual appeal, strengthen the brand character, and build brand awareness among the younger generation toward traditional food products.